2002
DOI: 10.1021/ef0102364
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary Recycling of Polyethylene to Hydrocarbon Fuel by Catalytic Cracking over Aluminum Pillared Clays

Abstract: The catalytic cracking of polyethylene over an Al pillared saponite, an Al pillared montmorillonite, and their regenerated samples was studied in a semi-batch reactor. Pillared clays were able to convert completely polyethylene in gaseous and liquid hydrocarbons, showing low coking levels. The selectivity and yield to liquid hydrocarbons were high, as the mild acidity of pillared clays avoided excessive cracking to small molecules. Regenerated catalyst samples showed practically identical levels of conversion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 15 publications
2
45
0
2
Order By: Relevance
“…Both natural clays and their aluminium oxide pillared analogues have also been tested for the catalytic cracking of polyethylene [49][50][51]. The clays investigated include montmorillonite and saponite.…”
Section: Heterogeneous Catalystsmentioning
confidence: 99%
“…Both natural clays and their aluminium oxide pillared analogues have also been tested for the catalytic cracking of polyethylene [49][50][51]. The clays investigated include montmorillonite and saponite.…”
Section: Heterogeneous Catalystsmentioning
confidence: 99%
“…Pillared clays have been tested in several applications: as catalysts for heavy oil upgrading [9][10][11], polyethylene catalytic cracking [12], denox processes [13], clean up of aqueous environments [14,15] and sorption of humic substances [16].…”
Section: Introductionmentioning
confidence: 99%
“…The first catalyst systems used in those works were well-established industrial acidic catalysts such as silica-alumina and zeolites, mainly Y-type. In the 1990s numerous studies have been carried out using as catalysts silica-alumina [5][6][7], zeolites [6][7][8][9][10][11], zeolite-based commercial cracking catalysts [12][13][14], MCM mesoporous materials [15] or clays and pillared clays [16,17] Besides the direct catalytic conversion of plastic, the subsequent in situ catalytic conversion of products of noncatalytic thermal degradation was also researched [18,19]. These studies have confirmed the superior quality of the hydrocarbon mixtures produced and highlighted the potential of catalytic degradation.…”
Section: Operation Modesmentioning
confidence: 88%
“…Generally over clays and pillared clays higher liquid yield values are reached than over zeolites [13,16,17]. Over US-Y zeolite values around 45% are achieved compared with values around 70% over clay-based catalysts.…”
Section: Conversion Liquid Yield Coke Contentmentioning
confidence: 91%
See 1 more Smart Citation